Ankle‐Brachial Index and Long‐Term (10 Years) Survival of Nondiabetic Hemodialysis Patients. Issue 3 (June 2016) - Bevc, Sebastjan; Purg, Darinka; Knehtl, Maša; Hren, Martin; Turnšek, Nina; Hojs, Nina; Zorman, Tadej; Dvoršak, Benjamin; Ekart, Robert; Hojs, Radovan
Abstract: Low (<0.9) and high (>1.4) ankle brachial index (ABI) is associated with a higher cardiovascular (CV) mortality in the general and hemodialysis (HD) population. The aim of our study was to determine the impact of ABI on long‐term survival of 52 non‐diabetic HD patients. The ABI was determined using an automated, non‐invasive waveform analysis device. Patients were divided into three groups: low (<0.9), normal (0.9–1.4) and high (>1.4) ABI. Patients were observed from the date of ABI measurement until their death or ten years. Survival analysis showed higher risk for CV death in HD patients with high ABI compared to normal ABI (log rank test P < 0.027). In Cox regression model adjusted for arterial hypertension, smoking, serum cholesterol and triglycerides, high ABI ( P < 0.049) remained a predictor of mortality. The results indicate an association between ABI and long‐term survival of non‐diabetic HD patients and only high ABI was associated with higher CV mortality.